Research on Splash Lubrication Characteristics of the Planetary Gear Train Based on the MPS Method - Shi Lubing; Chen Huixiao; Yan Shidang; Wang Jun; Ding Haohao; Pei Bang; Liu Zhongming; Wang Wenjian (Jixie chuandong)
In order to analyze the lubrication characteristics of the planetary gear transmission of shield main drive reducers, a simulation model of splash lubrication of the single-stage planetary gear train is established using the moving particle semi-implicit (MPS) method. By comparing the distribution of lubricating oil particles, velocity field, pressure field, the number of lubricating oil particles in the meshing area of gear teeth and the churning resistance moment produced by each rotating part during the planetary gear train movement under different working conditions, the influence of input speed, initial oil level height and oil temperature on the system lubrication effect and churning loss power are studied. The results show that the oil particle velocity and pressure increase with the increase of the input speed and oil level, and the low speed and oil level height will lead to the uneven distribution of oil particles in the reducer. The number of particles in the meshing zone between planetary gears, sun gears and inner gear rings decreases with the increase of input speed and oil temperature, and decreases with the decrease of oil level height. The meshing area of sun gears is the risk area of poor lubrication. The power loss of the system is most significantly affected by the input speed, and increases exponentially with the increase of the speed, while the influence of oil level height and oil temperature is relatively small. In each working condition, the churning loss power generated by the three planetary gears takes the largest proportion in the total churning loss power.